Normalista Nena Garcez : vida, formação e missão educacional (1898 - 1937) - Isidro, Thais Jussara de Oliveira Guedes (2023)
This thesis is a study in History of Education that aims to compose the life and training history of teacher Umbelina Garcez, also known as Nena, giving visibility to her as a historical subject who participated in the expansion of public education in the interior of Paraíba. Focused on the specificities and particularities of the life of this educator, we developed a biographical work that considers the relevance and relevance of research on the teaching profession because the individual itinerary is representative and, through it, it is also possible to apprehend the paths taken by the Paraíba educational system towards its structuring, since the formation of Nena Garcez as a student of the Normal School and her performance as a teacher of isolated chairs in the municipality of Mamanguape occurred concomitantly with the process of expansion and organization of the public education system of Paraíba. We also aim to understand the peculiar sociocultural dynamics of this temporality, expanding the look at the schooling processes, the current educational legislation, the power relations present in the educational interactions, the gender relations incident in the exercise of the teaching profession, in addition to the political and economic aspects of Paraíba education from 1898 to 1937. Tracing the trajectory of Professor Umbelina Garcez is justified by the possibility of bringing up and giving visibility to the life story of this educator, making the commitment to historically reconstruct the individual trajectory of a woman who contributed significantly to the development of education in Mamanguape - PB, but was not contemplated by official history. We use the New Cultural History as a theoretical framework for the development of research and Oral History as a methodology that permeates the studies undertaken through the testimony of family members, former students and acquaintances who lived with the teacher, although we point out the intersection with diverse documentary sources, such as official and unofficial documents, newspapers, periodicals, personal documents, books, photographs, among others. To epistemologically situate the research in the theoretical debates of contemporary historiography, we focus attention on the concepts of biography, life history, memory and orality, using the theoretical contributions of Dosse (2009), Levi (2006), Avelar and Schmidt (2012 and 2018), Loriga (2011), Nóvoa (1992, 2001, 2005) and Chartier (1994 and 1990). The Indicative Paradigm, a contribution by Ginzburg (1979), which raises the practice of tracking signs, clues and signs is also present in the research through the investigative stance that is assumed when following the traces left by the documents, speeches and testimonies that involve the researched teacher. A relevant historical record for the municipality of Mamanguape, the biography of Umbelina Garcez makes it possible to rescue the history of the first teacher to teach as an educator graduated from the Normal School and appointed by the public authorities in Mamanguape-PB, a city that despite having honored her by placing her name in a state school, little is known about her.